Experimental validation of vibration damping using an Archimedean spiral acoustic black hole. (27th October 2019) - Park, Seongmin; Kim, Minkyu; Jeon, Wonju
Abstract: Vibration damping in a thin structure can be effectively achieved by using an acoustic black hole (ABH), which is a straight wedge-shaped structure with power-law profile. However, it is difficult to apply the straight ABH to industrial system due to space limitations. In this study, we show that a spiral ABH whose baseline is rolled into an Archimedean spiral configuration can be an alternative for the straight ABH when an installation space for the ABH is limited. The spiral ABH is manufactured through a wire electric discharge machining, and its damping performance is validated experimentally. The experiments show large reductions of resonance peaks when compared to a reference uniform beam, indicating that the spiral ABH effectively reduces the structural vibration in the beam structure. Rolling the baseline into the spiral curve causes eigen-frequency shifts, but there is little difference in the damping performance between the spiral ABH and straight ABH. We further enhance the performance by increasing the spiral length and decrease the overall size of the spiral by reducing the spiral gap distance. The spiral ABH is expected to be a solution to apply the ABH to real-world problems such as damping vibration in various mechanical systems.